Morphological and molecular assessment of Lithophyllum okamurae with the description of L. neo-okamurae sp. nov. (Corallinales, Rhodophyta). Issue 2 (4th March 2022) - Kato, Aki; Basso, Daniela; Caragnano, Annalisa; Rodondi, Graziella; Le Gall, Line; Peña, Viviana; Hall-Spencer, Jason M.; Baba, Masasuke
ABSTRACT: Lithophyllum okamurae has been widely reported in the Pacific Ocean with identification based on morpho-anatomical observations. Two infraspecific taxa, L. okamurae f. okamurae and f. angulare, described from Japan, have been recorded in the temperate region of Japan. We assessed branched Lithophyllum samples morphologically referable to L. okamurae using morpho-anatomical data and DNA sequences ( psb A, rbc L and partial LSU rDNA) obtained from herbarium specimens, including type material, as well as recently field-collected material in Japan. The molecular analyses showed that these ' L. okamurae ' samples contained two species: L. okamurae and a cryptic new species which we describe as L. neo-okamurae sp. nov . Because the holotype of L. okamurae f. angulare was conspecific with original material cited in the protologue of L. okamurae, it is a heterotypic synonym of L. okamurae f. okamurae. Lithophyllum okamurae and L. neo-okamurae were morphologically similar in having warty, lumpy and fruticose thalli and in often forming rhodoliths. Lithophyllum okamurae can be morpho-anatomically distinguished from L. neo-okamurae by the thallus with tapering or plate-like protuberances (knobby protuberances in the latter) and by having smaller tetrasporangial conceptacle chambers (167–314 µm; 248–380 µm in L. neo-okamurae ). Our LSU rDNA sequence data from L. okamurae f. angulare (= L. okamurae f. okamurae ) was identical to that of the type of L. margaritae, which has nomenclatural priority over L. okamurae . However, considering that psb A and rbc L sequences of L. margaritae type material could not be generated in the present study, we refrain, for the moment, from proposing the taxonomic synonymy between these two taxa until the status of L. margaritae and its synonyms from the type locality (Gulf of California) are clarified.